The Contributions of Master Vien Minh to Theravāda Buddhism in Vietnam - Vo Mong Ben; Mahatthanadull, Sanu; Phramaha Nantakorn Piyabhani (The Journal of International Buddhist Studies College, 2024)
This research article examines the life, teachings, and contributions of Master Vien Minh to Theravāda Buddhism in Vietnam. The study employs documentary research methodology to address three primary objectives: (1) investigating Master Vien Minh’s life and works, (2) analyzing his application of the Buddha’s teachings to the daily lives of Vietnamese people, and (3) assessing his contributions to Theravāda Buddhism in Vietnam. The research reveals Master Vien Minh’s journey from an aspiring young monk to a influential Buddhist teacher and philosopher. It explores his unique approach to understanding and disseminating Buddhist principles, emphasizing the integration of dharma into everyday life. The study highlights his innovative meditation techniques and philosophical perspectives, which have made Buddhist teachings more accessible and relevant to Vietnamese practitioners. His philosophies about people and life include viewing life as an enlightened environment, seeing oneself as a wonderful scripture, living in accordance with cause and effect, obeying nature by returning dharma to dharma, and serving to perfection and perfection to serving. His meditation method for daily life involves dwelling in states of awareness. Furthermore, the research documents Master Vien Minh’s significant contributions to various aspects of Vietnamese society, including literature, education, charity, and social development, demonstrating the far-reaching impact of his work on the growth and sustainability of Theravāda Buddhism in Vietnam’s modern era.